OP0045 Synovial B Cell Status Determines Intensity of Rituximab Therapy Required in Rheumatoid Arthritis. (23rd January 2014) - Vital, E. M.; El-Sherbiny, Y.; Freeston, J.; Brown, A.; Reece, R.; Dass, S.; Buch, M.; Ponchel, F.; Emery, P.
Abstract : Background: Not all RA patients respond to a first cycle of rituximab. Previous synovial studies indicate that synovial B cells are depleted but higher pre- and post-treatment plasma cell numbers are associated with clinical non-response, as are higher numbers of plasmablasts in peripheral blood. Objectives: To find synovial determinants of plasma cell persistence and clinical response to rituximab Methods: 35 RF/CCP positive RA patients received licensed dose rituximab at baseline with a repeat cycle at 6 months in non-responders and at clinical relapse in responders. Peripheral blood B cell subsets were enumerated using flow cytometry. Knee synovitis was assessed using arthroscopic biopsy at baseline and 16 or 26 weeks and ultrasound power Doppler ultrasound (PDUS) at the same times. Synovial biopsies were analysed using immunohistochemistry for B cells (CD19) and plasma cells (CD138) with digital image analysis and real-time quantitative PCR (qPCR) using a 48 gene custom assay including genes for cell lineage markers, inflammatory cytokines, immunoglobulins, BAFF system molecules, chemokines and adhesion molecules. PDUS was scored semi-quantitatively 0-3 for 5 knee compartments and scores summated. qPCR data were analysed for relationships with IHC findings by Spearman's correlation with Bonferroni-Holms correction for multiple comparisons, and using hierarchical clustering. Results: IHC and qPCR both indicated a significant reduction in synovial B cells/CD19 mRNA but no significant overall change in plasma cells. CD138+ cell count after rituximab was associated with baseline CD138+ cell count and CXCL13 mRNA expression (R=0.738, p<0.001). Hierarchical clustering demonstrated a "B cell signature" in a subset of patients defined by clustering of high expression for CD19, CD138, CXCL13, BAFF receptor and immunoglobulin genes together with TNFalpha and IL-1. These patients had worse disease activity and clinical response. This was also marked on PDUS, which was almost completely abolished in patients without B cell signature. However, after a second cycle of rituximab, responses in the B cell signature group improved achieving a similar change in DAS28 from baseline as non-B cell signature patients. B cell signature patients had greater plasmablast repopulation in peripheral blood at 6 months (p=0.041). Conclusions: Outcome of rituximab treatment is worse in patients with high expression of synovial B cell markers and CXCL13, probably indicating aggregate or germinal centre synovial architecture. This appearance is associated with greater plasmablast repopulation in peripheral blood. "B cell signature" patients ultimately achieved the same response to rituximab as patients who do not have this synovial appearance, but needed more intensive therapy. Disclosure of Interest: None Declared